Seporsi Mie Ayam Karya Brian Khrisna Representasi Realitas Sosial: Kajian Sosiologisastra Ian Watt - Salma Fiddaraini (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2026)
Fish farming using the biofloc system is a technological innovation capable of increasing efficiency, production results, and the sustainability of fisheries business at the village level. This study aims to determine the development of fish farming businesses using the biofloc system in increasing family income in Sembuluh village. Then, it aims to understand the impact of using the biofloc system in increasing family income and to understand the Islamic economic perspective on the utilization of the biofloc system in increasing family income. The method used is a qualitative or field research approach with purposive sampling techniques to collect data from 5 fish farmers who implement the biofloc system. Data were collected through in-depth interviews, observation, and documentation, then analyzed descriptively. The research results show that fish farming using a biofloc system is able to increase family income through increased production and feed cost efficiency. This system supports more controlled pond management, maintains water quality, and produces more stable harvests. In addition to increasing income, the implementation of the biofloc system also strengthens family economic resilience due to planned harvest cycles and group cooperation. From an Islamic economic perspective, this practice aligns with the principles of halal, honesty, justice, and social responsibility, as well as providing benefits for families and the community.